Honor, Dignity and Business Reputation as Objects of the Protective Civil Law Relations in their Judicial Protection Against Defamation - POTAPENKO, Sergey Viktorovich (Journal of Advanced Research in Law and Economics, 2017)
Since not the law, in particular, article 152 of the Civil Code of the Russian Federation, nor the Russian judicial practice provide a legitimate definition of honor, dignity and business reputation, the courts, when considering defamation suits, use their doctrinal definitions based on the universal moral, not taking into account ethno-cultural, regional and other peculiarities of different parts of the Russian civil society, in particular these of the Cossacks of the Kuban Cossack Army. The article proves the need for a differentiated approach to the definition of the concepts of honor, dignity and business reputation in their judicial protection, taking into account that carriers of these intangible benefits belong to the individual structural groups and parts of civil society. The duty of the court is justified to formulate features underlying their conception of honor, dignity and business reputation in every particular case, since in civil law relations, these moral concepts transform into legal categories — objects of civil law relations in their judicial protection against defamation.
Keywords: honor; dignity; business reputation; defamation; judicial protection; the Kuban Cossack Army; the Cossacks